AB1084 Correlations Between Different Imaging Modalities in the Assessment of Acute Synovitis of the Wrist in Rheumatoid Arthritis: A Cross-Sectional Study. (9th June 2015) - Riis, R.G.C.; Kristensen, L.E.; Ellegaard, K.; Hangaard, S.; Bliddal, H.; Østergaard, M.; Boesen, M.
Abstract : Background: Rheumatoid arthritis (RA) is characterised by synovial inflammation and hypertrophy leading to progressive structural damage 1 . Synovitis can be difficult to detect by clinical examination. Therefore modern imaging of the affected joints plays a central role in the assessment of synovitis in RA 2 . Objectives: To correlate colour Doppler ultrasound (CDUS) with static and dynamic contrast-enhanced (CE) magnetic resonance imaging (MRI) in the assessment of synovitis of the wrist in patients with RA. Methods: Static and dynamic CE-MRI was performed in 36 patients with established RA and clinical arthritis of the wrist of which 32 also completed CDUS of the wrist. Doppler colour fraction (CF) was calculated as the sum of the maximum values in the radial, central and ulnar radiocarpal and intercarpal joints; synovitis and oedema were assessed on CE-MRI according to the OMERACT RA MRI scoring system (RAMRIS). On the dynamic CE-MRI (DCE-MRI), rough regions of interest were drawn around the wrist joints on the three central, coronal slices and collapsed into one. From the signal intensity graphs the following variables were automatically calculated: i) Initial Rate of Enhancement (IRE), i.e. the mean speed of enhancement, ii) Maximal Enhancement (ME), i.e. the mean of the highest signal intensity values, iii) Area Under the Curve (AUC), i.e. the area under the signal intensity curve and iv) Nvoxel, i.e. the number of voxels with plateau/washout patterns, which corresponds to the most perfused voxels. Results: 83.3% were females with a mean age of 58.6 years (SD:13.1). The mean baseline DAS28 score was 4.6 (SD:1.1). Spearman's test of rank correlation showed statistically significant correlations between all imaging variables (Table 1 ), with correlation coefficients well above 0.7 (p<0.001). In absolute numbers MExNvoxel and IRExNvoxel were the DCE-MRI variables with the strongest correlations to Doppler CF, whereas the RAMRIS synovitis score was slightly stronger correlated to Doppler CF than the bone oedema score. Conclusions: Ultrasound colour Doppler, static and dynamic CE-MRI are highly correlated in the assessment of synovitis in the wrist, and may all be useful modalities to complement the clinical examination. References: McInnes IB et al.The pathogenesis of rheumatoid arthritis.N Engl J Med 2011; 365(23):2205-2219. Tan YK et al.Imaging in rheumatoid arthritis.Best Pract Res Clin Rheumatol 2011;25(4):569-584. Acknowledgements: We thank Image Analysis LTD for technical support in analysing the DCE-MRI and the Dept of Radiology, Bispebjerg-Frederiksberg Hospital, in acquiring the MRI. Disclosure of Interest: R. G. C. Riis Grant/research support from: This study was supported by unrestricted grants from the Oak Foundation and AbbVie, L. E. Kristensen Grant/research support from: This study was supported by unrestricted grants from the Oak Foundation and AbbVie, K. Ellegaard Grant/research support from: This study was supported by unrestricted grants from the Oak Foundation and AbbVie, S. Hangaard Grant/research support from: This study was supported by unrestricted grants from the Oak Foundation and AbbVie, H. Bliddal Grant/research support from: This study was supported by unrestricted grants from the Oak Foundation and AbbVie, M. Østergaard: None declared, M. Boesen Grant/research support from: This study was supported by unrestricted grants from the Oak Foundation and AbbVie